Editor's Introduction: Juvenile Delinquency, Modernity, and the State - Ellis, Heather (Social justice, 2011)
The article presents an introduction to the December 2012 issue of "Social Justice" focusing on the relationship between the construction of juvenile delinquency, state-sponsored social programs and relations, and the impact of modernity and World War II on social structure.